Phylogeography of Rattus norvegicus in the South Atlantic Ocean - Hingston, Melanie; Poncet, Sally; Passfield, Ken; Tabak, Michael A.; Gabriel, Sofia I.; Piertney, Stuart B.; Russell, James C. (Diversity, 2016)
Acknowledgments Funding for sample collection was provided by the Shackleton Scholarship Fund, Antarctic Research Trust, the Wyoming Biodiversity Institute, PVE/CAPES (Proposal 235453) and Fundação para a Ciência e a Tecnologia (SFRH/BPD/88854/2012). Thanks to Martin Collins, Andy Black, Darren Christie and the Government of South Georgia and South Sandwich Islands for the provision of samples from South Georgia, Annalea Beard for providing the rat sample from St Helena Island, Joaquim Tapisso, Rita Monarca and Ana Cerveira for samples from Portugal, and Emily Puckett for help validating South American SNP haplotypes. Funding for DNA sequencing was provided by Island LandCare, the University of Auckland. Thanks to two anonymous reviewers for the constructive comments. Peer reviewed